2017
DOI: 10.1515/cdbme-2017-0112
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of a bias in apparent exchange rate measurement

Abstract: Double diffusion encoding (DDE) MRI is a technique in which two diffusion weighted periods are applied between excitation and acquisition. This allows to acquire structural information (as pore size and shape) and molecular exchange between compartments, in terms of apparent exchange rate (AXR). However, it has not been well investigated yet whether the diffusion restriction underlying DDE size estimation may compromise AXR results.Numerical simulations for impermeable spheres have shown that in case of small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“… 32 , 93 , 94 , 95 , 96 Note that this implies that waveforms that lie along the exchange axis of the restriction‐exchange space (such as FEXI) may become sensitive to restricted diffusion in environments with large structures. Indeed, previous work has shown that restricted diffusion can bias exchange rate estimates, 97 which we refer to here as crosstalk (Figure 6 ). It is also worth noting that the bias in estimates observed with the current approach can in part be attributed nonzero intracompartmental kurtosis, which challenges the assumptions of the signal representation.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 93 , 94 , 95 , 96 Note that this implies that waveforms that lie along the exchange axis of the restriction‐exchange space (such as FEXI) may become sensitive to restricted diffusion in environments with large structures. Indeed, previous work has shown that restricted diffusion can bias exchange rate estimates, 97 which we refer to here as crosstalk (Figure 6 ). It is also worth noting that the bias in estimates observed with the current approach can in part be attributed nonzero intracompartmental kurtosis, which challenges the assumptions of the signal representation.…”
Section: Discussionmentioning
confidence: 99%